Collective efficiency strategies: a policy instrument solution to boost competitiveness in low-density territories - Rui Nuno Baleiras (European Regional Science Association (ERSA), 2011)
This paper motivates the focus of EU cohesion policy at large and the territorial cooperation tools on the economic development of territories featuring impoverishing growth associated to low population density. An innovative policy approach to help solving this problem in many Member States is put forward here. It is based on the economic concept of "collective efficiency". It should be understood as a proposal to improve EU cohesion policy in the next programming period. As such, the paper suggests actual ideas to be included in the forthcoming Common Strategic Framework and Development and Investment Partnership Contracts.
Keywords: 330